Design of Laser Activated Antimicrobial Porous Tricalcium Phosphate-Hydroxyapatite Scaffolds for Orthopedic Applications - Filipov, Emil; Yildiz, Ridvan; Dikovska, Anna; Sotelo, Lamborghini; Soma, Tharun; Avdeev, Georgi; Terziyska, Penka; Christiansen, Silke; Leriche, Anne; Fernandes, Maria Helena; Daskalova, Albena (Journal of Functional Biomaterials, 2024)
The field of bone tissue engineering is steadily being improved by novel experimental approaches. Nevertheless, microbial adhesion after scaffold implantation remains a limitation that could lead to the impairment of the regeneration process, or scaffold rejection. The present study introduces a methodology that employs laser-based strategies for the development of antimicrobial interfaces on tricalcium phosphate–hydroxyapatite (TCP-HA) scaffolds. The outer surfaces of the ceramic scaffolds with inner porosity were structured using a femtosecond laser (λ = 800 nm; τ = 70 fs) for developing micropatterns and altering local surface roughness. The pulsed laser deposition of ZnO was used for the subsequent functionalization of both laser-structured and unmodified surfaces. The impact of the fs irradiation was investigated by Raman spectroscopy and X-ray diffraction. The effects of the ZnO-layered ceramic surfaces on initial bacterial adherence were assessed by culturing Staphylococcus aureus on both functionalized and non-functionalized scaffolds. Bacterial metabolic activity and morphology were monitored via the Resazurin assay and microscopic approaches. The presence of ZnO evidently decreased the metabolic activity of bacteria and led to impaired cell morphology. The results from this study have led to the conclusion that the combination of fs laser-structured surface topography and ZnO could yield a potential antimicrobial interface for implants in bone tissue engineering.
CRIS-Team Scopus Importer:2024-03-08
Keywords: antimicrobial; bone tissue engineering; femtosecond laser processing; pulsed laser deposition